2022
DOI: 10.1155/2022/4637594
|View full text |Cite|
|
Sign up to set email alerts
|

Online Troll Reviewer Detection Using Deep Learning Techniques

Abstract: The concentration of this paper is on detecting trolls among reviewers and users in online discussions and link distribution on social news aggregators such as Reddit. Trolls, a subset of suspicious reviewers, have been the focus of our attention. A troll reviewer is distinguished from an ordinary reviewer by the use of sentiment analysis and deep learning techniques to identify the sentiment of their troll posts. Machine learning and lexicon-based approaches can also be used for sentiment analysis. The novelt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
(36 reference statements)
0
7
0
Order By: Relevance
“…In 2022, Al-Adhaileh, et.al, [19] have presented Online Troll Reviewer Detection Utilizing DL Methods. Here, emphasis was on identifying clowns among consumers and reviewers in discussion groups and link-sharing on social media aggregators like Wikipedia.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2022, Al-Adhaileh, et.al, [19] have presented Online Troll Reviewer Detection Utilizing DL Methods. Here, emphasis was on identifying clowns among consumers and reviewers in discussion groups and link-sharing on social media aggregators like Wikipedia.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The percentage of true negatives that the method correctly identifies is called specificity. It is given in equation (19),…”
Section: ) Specificitymentioning
confidence: 99%
“…The four gates are input i t , forget f t , cell state c t , and output gate o t . The equations for these gates are as follows [41][42][43][44][45][46]:…”
Section: Bilstm Layersmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%